Similarity and Difference of Phase Transition FCC – BCC in Calcium and Strontium - V.V. Pozhivatenko (Журнал нано- та електронної фізики)
Features of polymorphism in calcium and strontium from the point of view of similarity of physical processes which occur at change of pressure and temperatures are researched. The known experimental facts are added calculated (first principal and fit) by results which illustrate both similarity, and difference of structural phase transitions FCC – BCC in calcium and strontium. The increase in similarity of the effects connected with polymorphism is shown, at increase both pressure, and temperatures.